Spatial mass customization: Mass-Customisable Urban Spaces and Spatial Entities - Farr, Eric R. P. (Mass Customisation and Personalisation in Architecture and Construction, 2013)
Mass customisation is a well-known strategy for responding to diverse needs, preferences, and requirements. Its manifestations in the built environment and, more specifically, in urban studies, however, have remained almost untouched. Urban spaces and entities have some potentialities and capacities that make them or their compartments open to the application of mass customisation. Pursuing a systemised approach to mass customisation (MC) in urban studies not only enables the organisation of more resilient types and more responsive modes of urban spaces and entities but also assists managerial and organisational bodies to improve the efficiency, versatility, and flexibility of urban contexts. This chapter explores why and how MC of urban spaces and entities - what I shall call spatial mass customisation (spatial MC) - can be supported. Defining spatial MC and identifying its means, aspects, and manifestations, the chapter investigates the types of urban spaces that can absorb mass as well as those urban entities with capacities for being customised. It then identifies the customisability of those urban entities that can be used to design, enhance, or modify urban spaces. It explores how mass-customisable aspects of urban spaces and their compartments can be recognised and categorised by providing case examples.